Pengaruh Proper Rating, Industrial Type dan Profitabilitas Terhadap Carbon Emission Disclosure Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Dewi, I Gusti Ayu Agung Omika; Aldhani, Luh Gede Putu Risadhi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to examine the effect of PROPER rating, industrial type and profitability on carbon emission disclosure. The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange with a research period 2017-2019. The method of sample selection is done by purposive sampling. Only 35 companies meet the criteria. The hypothesis in this study was tested using F test and t test. The data analysis technique used in this study is the classic assumption test and multiple linear regression test.Â The results of the study showed that all variables were declared free of interference from existing classical assumptions. From the result of multiple linear regression tests the results of the f test are obtained at 15,165 with a significant value of 0,001 or < 0,05. This means that PROPER Rating, Industrial Type and Profitabilitas on Carbon Emission Disclosure in Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2019 have a significant simultaneous effect. Partial testing shows the results that all independent variables have a significant effect on carbon emission disclosure.